Summary of biological research on hepatoblastoma: a scoping review - Wang, Huan-sheng; Lao, Jing; Jiang, Ren-sen; Wang, Bin; Ma, Xiao-peng; Wang, Jian-yao (Frontiers in Pediatrics, 2024)
Background: Hepatoblastoma is the most prevalent primary hepatic malignancy in children, comprising 80% of pediatric hepatic malignancies and 1% of all pediatric malignancies. However, traditional treatments have proven inadequate in effectively curing hepatoblastoma, leading to a poor prognosis. Methods: A literature search was conducted on multiple electronic databases (PubMed and Google Scholar). A total of 86 articles were eligible for inclusion in this review. Result: This review aims to consolidate recent developments in hepatoblastoma research, focusing on the latest advances in cancer-associated genomics, epigenetic studies, transcriptional programs and molecular subtypes. We also discuss the current treatment approaches and forthcoming strategies to address cancer-associated biological challenges. Conclusion: To provide a comprehensive summary of the molecular mechanisms associated with hepatoblastoma occurrence, this review highlights three key aspects: genomics, epigenetics, and transcriptomics. Our review aims to facilitate the exploration of novel molecular mechanisms and the development of innovative clinical treatment strategies for hepatoblastoma.